DESCRIPTION OF NUTRITION STATUS BASED ON THE BREAKFAST KNOWLEDGE LEVEL AND BREAKFAST CONSUMPTION STUDENTS OF THE SIDEMENT 2ST MIDDLE SCHOOL KARANGASEM DISTRICT - I Gusti Agung Mirah Wiratmini; I Ketut Kencana; I Putu Suiraoka (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
Nutritional status is primarily affected by infectious diseases and nutrient intake. The intended intake is breakfast Breakfast intake is influenced by the level of knowledge related to breakfast. This study aims to determine; (1) knowing nutritional status; (2) get an overview of the level of knowledge of breakfast; (3) get an overview of breakfast consumption; (4) get an overview of nutritional status based on the level of knowledge of breakfast; (5) get a description of nutritional status based on breakfast consumption. The type of research is cross sectional, where the research was conducted in SMP Negeri 2 Sidemen, Karangasem Regency and the time of the study in February-May 2019 with a population of 186 and taking the study sample as many as 64 (35%). The results of the study show that; (1) The tendency of samples with normal nutritional status (71.,88%); (2) The tendency of knowledgeable samples to have sufficient breakfast (53,13%); (3) The tendency of the sample to have a good intake of energy, protein, and fat breakfast; (4) There is a tendency between nutritional status and knowledge of breakfast; (5) There is a tendency between nutritional status and consumption of energy, protein, and breakfast fat samples. Keywords: Nutritional Status, Breakfast Knowledge, Breakfast Consumption.